Serum Uric Acid and Its Association with Coronary Artery Disease - Akanda, MAK; Choudhury, KN; Ali, MZ; Naher, S; Islam, ASME; Ali, MI (Cardiovascular Journal, 2012)
Background: Few studies have assessed the relation of uric acid level with the severity of coronary artery disease (CAD). This study investigated the association between high uric acid levels with the presence and severity of CAD. Materials and Methods: This study was designed as an observational cohort study. The study was composed of 180 patients admitted at our institution due to symptoms related to CAD. Patients having angiographic evidence of stenosis in coronary artery were as case group and without stenosis control group. Patients with high uric acid (hyperuricemia) were defined as serum uric acid concentration ?7.0mg/dl or ?420 ?mol/L in men and ?6mg/dl or ?360 ? mol/L in women. The presence of CAD has been defined as the Gensini score being ?1. Results: There was a statistically significant difference between the mean uric acid levels of patients with and without CAD (358.23±71.11 ?mol/l vs251.32±54.92 ?mol/l respectively, p<0.001). There was a statistically significant difference between ejection fraction of patients with and without CAD (54.50±9.25 vs. 63.16±6.56 respectively, p?0.001). Spearman correlation analysis demonstrated a positive correlation between the serum uric acid level and the severity of CAD (p=?0.001, r=0.39). When patients were classified into four groups according to their Gensini score, mean serum uric acid level was found to be significantly increased across the tertiles, and a statistically significant difference was detected between the tertiles (p= ?0.001). Conclusion: In conclusion, a significant association has been found between serum uric acid level and the presence and severity of CAD. In addition to the evaluation of conventional risk factors in daily clinical practice, the measurement of uric acid level might provide significant prognostic benefits in terms of global cardiovascular risk and management of the patients. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12206 Cardiovasc. j. 2012; 5(1): 12-17